The Impact of The Availability of Integrated Information on The Success of The Competitive Strategy - Mohamed, Mohamed Khalil Hamid; Abdul Jalil, Mohammed Hassan Mohammed (Journal of Economic, Administrative and Legal Sciences, 2018)
This study aimed studying the impact of the integrated business reports in providing information to evaluate the competitive strategy in the Sudanese environment. The study used both the analytical descriptive approach and the case study approach. The study concluded that the financial statements prepared according to integrated business reports provide information on the activities of the competing companies, thus contributing to achieving a sustainable competitive advantage. The study has recommended that the board of directors should consider preparing the integrated business reports because of their effect on the company's performance and value through the environmental, social and judicial information.
Keywords: integrated business reports; competitive strategy; leadership strategy at all costs; excellence strategy; focus strategy